WHEN LAW TRANSCENDS THE JUDICIAL COMPETENCE: THE SUBJECTIVE EFFECTIVENESS OF THE SENTENCE IN CLASS ACTIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to analyze the subjective effects of the sentence in class actions, especially after the legislative change promoted in the Public Civil Action Law. The problem that we intend to face is about the impossibility of restricting the subjective effectiveness of res judicata, starting from the hypothesis that the legislative change, which is aimed precisely at this restriction, can create instability and divergence between different judicial decisions, although handed down in disputes with the same object. To achieve the proposed purpose, in the first subtitle the objective limits of the sentence pronounced in the collective process will be analyzed. In the second subtitle, the subjective limits of the sentence handed down in the collective process will be analyzed. The third subtitle will analyze the subjective effects of the sentence in class actions after the amendment of article 16 of the Public Civil Action Law. In the fourth subtitle, the doctrinal criticisms of the amendment of article 16 of the Public Civil Action Law will be analyzed. In the fifth subtitle, the jurisprudential interpretation and the unconstitutionality of article 16 of the Public Civil Action Law will be analyzed, as amended by Law nº 9.494/97. The research found that the change in article 16 of the Public Civil Action Law could cause several problems, mainly related to the violation of isonomy and the effectiveness of judicial provision. The methodology used was analytical-deductive. Corresponding judicial decisions and the discussion on the theme that makes up the object of the article were analyzed, backed by books, scientific articles, and doctrine, to reach the indicated results